Ultrastructural Changes of Coronary Artery Endothelium Associated with Biliary Obstruction in the Rat - Gutstein, W. H. (1973)
Ultrastructural cellular changes in various target organs have been described in association with experimentally induced biliary obstruction. In the present study, the effect of bile duct ligation on coronary artery endothelium was examined in rats 24 hours after surgery. Electron microscopic examination revealed marked degenerative changes of endothelial cells compared with the lack of such alterations in control animals. Some possible implications of the reported observations for atherogenesis are discussed.